Quality of life after surgery for rectal cancer: a systematic review of comparisons with the general population. (October 2015) - Giandomenico, Francesca; Gavaruzzi, Teresa; Lotto, Lorella; Del Bianco, Paola; Barina, Andrea; Perin, Alessandro; Pucciarelli, Salvatore
Abstract : Rectal cancer treatments may impact negatively on patients' bowel and sexual functions and, in turn, on health-related quality of life. Information on the likely effects of treatment is essential in order to facilitate the care process and the adaptation of patients to their condition. Studies that report on the comparison between rectal cancer patients and the general population are a useful source of this evidence, providing elements to aid in answering questions such as 'is my life going to be the same as before?' In this article, the authors have systematically reviewed articles published in the last 6 years that report on the comparison between rectal patients' and the general population's health-related quality of life. Sixteen out of 645 articles were included. The results are summarized and critically discussed.